National Accounting Culture and Its Effect on Financial Reporting in a Globalized World Research in Progress - Katarzyna KOLESNIK (Communications of International Proceedings, 2025)
The primary objective of this study is to investigate the impact of culture (as measured by Hofstede) on disclosures in financial statements prepared under International Financial Reporting Standards (IFRS) by firms from different countries. The sample will comprise 2021-2023 consolidated financial statements of listed companies (excluding banks, insurance, and other financial institutions) from three countries representing different cultural areas: the United Kingdom (Anglo), Germany (Germanic) and Poland (Central Eastern Europe, CEE). We will empirically test whether the cultural values have a significant impact on financial disclosures even after the use of IFRS. The paper is one of the few comparative studies attempting to assess the effects of culture on financial disclosures in Western Europe countries and CEE countries. Most of the international comparative studies in this research area have neglected CEE countries.
Keywords: disclosures; culture; IFRS